Sharia Label and Conventional Practice: A Critical Evaluation of the Islamic Pawnshop Rahn Contract - Abdul Nafi' Nurfauzan; Ahmad Zaki Al Fanani; Irawan; Muhammad Mahalli Rofii (Journal of Islamic Economic Studies, 2026)
The post-digitalization expansion of the Islamic pawnshop industry poses a dilemma for Islamic Financial Institutions (IFIs) between commercial imperatives and substantive compliance. A critical issue arises regarding the application of hybrid contracts (rahn and ijarah) in gold pawning products, which are prone to devolving into disguised usurious (ribawi) practices for the sake of revenue generation. This study aims to analyze the Sharia validity of these contract constructions and the consistency of the determination of the rental fee (ujrah) with Fatwa DSN-MUI No. 25/DSN-MUI/III/2002 and the principles of justice outlined in OJK Regulation (POJK) Number 39 of 2024. Utilizing a qualitative method with a normative juridical approach, alongside Maqasid Al-Shariah and Substance over Form analyses, this research identifies significant disparities in practice. Certain IFIs calculate ujrah based on the loan ceiling rather than the collateral's physical value. This practice materially contravenes the fatwa and indicates the use of legal stratagems (hilah) to replicate interest mechanisms amidst liquidity pressures. The study concludes that the Sharia label on gold pawning products is frequently confined to administrative formalities, lacking substantive justice. Consequently, regulators are urged to reform tariff regulations by explicitly prohibiting the use of loan ceiling variables in fee determination to ensure Sharia integrity.